2020
DOI: 10.2196/22624
|View full text |Cite
|
Sign up to set email alerts
|

Topics, Trends, and Sentiments of Tweets About the COVID-19 Pandemic: Temporal Infoveillance Study

Abstract: Background With restrictions on movement and stay-at-home orders in place due to the COVID-19 pandemic, social media platforms such as Twitter have become an outlet for users to express their concerns, opinions, and feelings about the pandemic. Individuals, health agencies, and governments are using Twitter to communicate about COVID-19. Objective The aims of this study were to examine key themes and topics of English-language COVID-19–related tweets po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
198
4
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(222 citation statements)
references
References 25 publications
15
198
4
5
Order By: Relevance
“…People might develop positive emotions and self-efficacy in coping with this public health threat. For example, sentiment analysis based on COIVD-19 related tweets from January to May 2020 suggested a reversal of sentiments from negative to positive for topics such as public prevention, government response, impact on healthcare industry, and COVID-19 treatment and recovery (Chandrasekaran et al, 2020)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People might develop positive emotions and self-efficacy in coping with this public health threat. For example, sentiment analysis based on COIVD-19 related tweets from January to May 2020 suggested a reversal of sentiments from negative to positive for topics such as public prevention, government response, impact on healthcare industry, and COVID-19 treatment and recovery (Chandrasekaran et al, 2020)…”
Section: Discussionmentioning
confidence: 99%
“…Chandrasekaran and colleagues conducted text mining of COVID-19-related English tweets from January to May 2020 to group the main topics and uncover the key trends by examining sentiment (positive or negative) scores. (Chandrasekaran, Mehta, Valkunde, & Moustakas, 2020) Dyer and Kolic developed indicators of public risk perception based on emotion and attention presented in tweets from 12 countries between March and June 2020. Twitter users showed differential sensitivity by country to national COVID-19 death rates.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to that, there are very few research that has combined both topic modeling and sentiment analysis to investigate COVID-19 data. Chandrasekaran et al [26] discussed topics, trends, and sentiments of tweets about the COVID-19 pandemic using tools such as LDA and VADER. Xue et al [27] analyzed tweets to understand public discourse and sentiment during COVID-19 pandemic.…”
Section: Topic Modeling and Sentiment Analysismentioning
confidence: 99%
“…Revealed by the quantity of tweets, the public's most prominent concern was death, with over 22.79% of tweets relating to death-related discussion. Previous infoveillance studies of Twitter data in the early period of COVID-19 found that 4.34% of tweets were about death reporting [ 45 ] and 10.54% of tweets pertained to deaths caused by COVID-19 [ 29 ]. The substantial increase in the death-related discussion with the progression of the pandemic highlighted the urgency of communicating adjusting information to the public, which refers to the information helping them to cope psychologically in threatening situations [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This echoed past crisis research: in risky environments, the first information that should be conveyed to the public is the information that instructs the public on how to protect themselves in the threatened environments [ 46 ]. It also showed that taking actions to prevent the virus from spreading, such as wearing masks and observance of social distancing orders, is a constant topic of the public from the prepandemic period to the peripandemic period [ 29 , 45 ]. The CDC’s instructions on how to act in the context of the COVID-19 pandemic, such as guidelines for reopening, recommendations on wearing masks, and how to make masks, have successfully attracted the public attention as soon as they were released.…”
Section: Discussionmentioning
confidence: 99%